Laparoscopic versus open colorectal surgery in the acute setting (LaCeS trial): a multicentre randomized feasibility trial. Issue 12 (23rd June 2020) - Harji, D. P.; Marshall, H.; Gordon, K.; Twiddy, M.; Pullan, A.; Meads, D.; Croft, J.; Burke, D.; Griffiths, B.; Verjee, A.; Sagar, P.; Stocken, D.; et al.
Abstract : Background: Approximately 30 000 people undergo major emergency abdominal gastrointestinal surgery annually, and 36 per cent of these procedures (around 10 800) are carried out for emergency colorectal pathology. Some 14 per cent of all patients requiring emergency surgery have a laparoscopic procedure. The aims of the LaCeS (laparoscopic versus open colorectal surgery in the acute setting) feasibility trial were to assess the feasibility, safety and acceptability of performing a large‐scale definitive phase III RCT, with a comparison of emergency laparoscopic versus open surgery for acute colorectal pathology. Methods: LaCeS was designed as a prospective, multicentre, single‐blind, parallel‐group, pragmatic feasibility RCT with an integrated qualitative study. Randomization was undertaken centrally, with patients randomized on a 1 : 1 basis between laparoscopic or open surgery. Results: A total of 64 patients were recruited across five centres. The overall mean steady‐state recruitment rate was 1·2 patients per month per site. Baseline compliance for clinical and health‐related quality‐of‐life data was 99·8 and 93·8 per cent respectively. The conversion rate from laparoscopic to open surgery was 39 (95 per cent c.i. 23 to 58) per cent. The 30‐day postoperative complication rate was 27 (13 to 46) per cent in the laparoscopic arm and 42 (25 to 61) per cent in the open arm. Conclusion: Laparoscopic emergency colorectal surgery may have an acceptable safety profile. Registration number: ISRCTN15681041 ( http://www.controlled‐trials.com ). Abstract : The LaCeS feasibility trial has demonstrated that it is possible to evaluate laparoscopic surgery in the emergency colorectal setting within the context of an RCT. It has also shown that it is possible to recruit to a surgical trial in the emergency setting, with good compliance to trial procedures and processes, and overall acceptability by patients and clinicians. Nicely tied LaCeS Abstract : Antecedentes: Aproximadamente 30.000 personas se someten cada año una operación de cirugía mayor urgente gastrointestinal de las cuales el 36% (~ 10.800) se realizan por patología colorrectal urgente. Aproximadamente el 14% de todos los pacientes que requieren cirugía urgente son operados mediante abordaje laparoscópico. Los objetivos del ensayo de factibilidad LaCeS ( Laparoscopic versus Open Colorectal Surgery in the Acute Setting ; Cirugía Colorrectal Laparoscópica versus Abierta en Urgencias) fueron evaluar la factibilidad, seguridad y aceptabilidad de realizar un ensayo clínico aleatorizado definitivo a gran escala de fase III comparando la cirugía colorrectal urgente por vía laparoscópica con el abordaje abierto. Métodos: LaCeS se diseñó como un ensayo clínico prospectivo, multicéntrico, simple ciego, de grupos paralelos, pragmático, aleatorizado (factibilidad) con un estudio cualitativo integrado. La asignación al azar se realizó de forma centralizada y los pacientes se asignaron al azar en proporción 1:1 a cirugía laparoscópica o abierta. Resultados: Un total de 64 pacientes fueron reclutados en 5 centros. La tasa media global estable de reclutamiento fue de 1, 2 pacientes/mes. El cumplimiento inicial de los datos clínicos y de calidad de vida (HRQoL) fue del 99, 8% y del 93, 8%, respectivamente. La tasa de conversión de la cirugía laparoscópica a cirugía abierta fue del 39, 4% (i.c. del 95%: 22, 9% a 57, 9%). La tasa de complicaciones postoperatorias a los 30 días fue del 27, 3% (i.c. del 95%: 13, 3‐45, 5) para la cirugía laparoscópica y del 41, 9% (i.c. del 95%: 24, 6‐60, 9) para la cirugía abierta. Conclusión: La cirugía colorrectal urgente por vía laparoscópica puede tener un perfil de seguridad aceptable.